ANALISIS PENGARUH SARANA PRASARANA, PROSES PEMBELAJARAN DAN PERSEPSI ORANG TUA SISWA TERHADAP KUALITAS PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 TINGKAT SEKOLAH DASAR DI KOTA DENPASAR - Pancarya, Gede; Widiana, I Nyoman Wahyu; Supartha, I Nyoman (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to analyze the influence of the learning process, facilities and infrastructure, and the parent’s perceptions on the quality of learning quality during the COVID-19 pandemic at the elementary school level in Denpasar city. The practitioner took 25 elementary schools in each sub-district, which consisted of 13 public elementary schools and 12 private elementary schools. In this study, samples were taken from parents of elementary school students in grade 1, because grade 1 were students who needed more guidance from parents to carry out learning activities boldly. This research method is quantitative, validity and reliability test, multiple regression analysis and t test and f test. The data collection technique used a questionnaire distribution technique. The instrument used in collecting data in this study was a questionnaire. The data analysis technique in this study is multiple regression with SPSS. The results of the descriptive analysis showed that the learning process variable (X1) had a minimum score of 12, a maximum score of 25, an average score of 20.04 with a standard deviation of 3.025. The Facility and Infrastructure (X2) variable has a minimum score of 10, a maximum score of 25, an average score of 19.16 with a standard deviation of 3,287. Parents' Perception Variable (X3) has a minimum score of 12, a maximum score of 25, an average score of 18.94 with a standard deviation of 3.443. The learning quality variable (Y) has a minimum score of 15, a maximum score of 25, an average score of 20.04 with a standard deviation of 2.474. The conclusion from this data analysis is that the learning process has a positive and significant effect on the quality of learning, Facilities and Infrastructure have a positive and significant effect on the quality of learning, the perception of parents has a positive and significant effect on the quality of learning. The suggestions that can be given are expected to be used as a basic reference in the Quality of Learning. There are several things that can be done to improve the quality of learning quality by paying attention to and improving the learning process, facilities and infrastructure, and parents' perceptions